Jaksel Slang as the Social Status of Teenager in Jakarta - Tarigan, Aloina Majesty (Gema Wiralodra, 2023)
Language in everyday life is a communication tool that is heavily influenced by the culture and background of social actors and forms a new identity for those who use it. The existing diversity of languages then forms new things and involves cultural assimilation, so that the use of bilingualism and multilingualism is found which is often found even in daily conversations. In its development, language then creates complex phenomena that affect social statutes in society and in social interaction. The use of South Jakarta Slang places its users in a certain social status so that they are considered more slang. Slang is moving into the culture of people by switching code not only to put the level of interaction, but also to give a more appropriate impression because there are some words that are more appropriate to use in their explanations. Everyone is expected to be able to use any type or style of slang, but must see who is the subject of the other person because language is very important and is one of the tools of communication, so don't trigger conflicts due to disagreements in using language.